Hormonal influence on the effect of mirabegron treatment for overactive bladder. Issue 12 (December 2016) - Kallner, Helena Kopp; Elmér, Caroline; Andersson, Karl-Erik; Altman, Daniel
Abstract: Objective: The aim of this study was to evaluate if levels of gonadotropic and sex steroidal hormones influence the efficacy of mirabegron in the treatment of overactive bladder. Methods: We included 58 female participants who received treatment with mirabegron 50 mg once daily and provided a blood sample for hormone profiling before treatment was initiated. Serum hormone concentrations for estradiol, progesterone, testosterone, FSH, LH, TSH, and T4 were analyzed. Urinary Distress Inventory (UDI), (overactive bladder domain: UDIOAB ), and the short form Pelvic Floor Impact Questionnaire (PFIQ-7) were used to assess subjective outcomes. Results: There were significant overall improvements in UDI, UDIOAB, and the PFIQ from baseline to the 2 months of follow-up ( P  = 0.001, 0.001, and 0.008, respectively). The magnitude of the mean difference of improvements was similar between pre- and postmenopausal women. Estrogen levels were nonsignificantly lower in participants who experienced an improvement in UDI and UDIOAB at 2 months of follow-up as compared with those that did not ( P  = 0.7). There were no other clinically relevant differences in hormone levels in relation to improvements in UDI, UDIOAB, or PFIQ. In logistic regression analysis there were no associations between UDIOAB outcomes and age, previous use of anticholinergic drugs, parity, menopause, and local estrogen treatment. Conclusions: Estradiol, gonadotropic hormones, thyroid hormones, and testosterone levels did not influence the clinical effects of mirabegron in women with overactive bladder. Menopause status should not be a determinant for mirabegron treatment.